The Effect of Human Capital and Unemployment on Poverty Through Economic Growth and The Moderating Role of Investment - Dahliah, Dahliah (Jurnal Ekonomi Kuantitatif Terapan; 2023: Vol. 16, No. 1, Februari 2023 (pp.1-186), 2023)
The aims of this study are: (1) to analyze the effect of human capital and unemployment on economic growth. (2) analyze the effect of human capital, unemployment, and economic growth on poverty. (3) analyze the effect of human capital and unemployment on poverty through economic growth. (4) analyze the effect of investment moderation between human capital on economic growth. (5) analyze the effect of investment moderation between unemployment and poverty. The approach used in this study uses a quantitative approach. The data is secondary data sourced from the Indonesian Central Statistics Agency and the Central Statistics Agency of South Sulawesi in 2021. The data collection method uses secondary data from documentation related to years of education, unemployment, foreign and domestic capital investment, and Gross Domestic Product. Regional (GDP) and the number of poor people in South Sulawesi Province for 2017-2021. The analytical method uses descriptive statistics, classical assumption, path analysis, and Sobel. The study's results prove that: (1) Human capital positively and significantly affects economic growth. (2) Unemployment has a negative and significant effect on poverty. (3) Human capital has a negative and significant effect on poverty. (4) Unemployment has a positive and significant effect on poverty. (5) Economic growth has a negative and insignificant effect on poverty. (6) Human capital positively and significantly affects poverty through economic growth. (7) Unemployment positively and significantly affects poverty through economic growth. (8) Investment can positively and significantly moderate the relationship between human capital and economic growth. (9) Investment can positively and significantly moderate the relationship between unemployment and poverty.